Evaluasi Desain dan Potensi Pemanfaatan Kembali Hunian Transisi: Dua Dekade Pasca-tsunami Aceh - Karima Adilla (Prodi Arsitektur, Fakultas Sains dan Teknologi bekerja sama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The housing destruction caused by the 2004 Aceh earthquake and tsunami led to the large-scale construction of transitional shelters intended for short-term use prior to permanent resettlement. Although these shelters were designed with a lifespan of only two to three years, a significant number remain standing two decades later. This study re-examines the long-term condition, transformation, and reuse potential of transitional shelters in Aceh, addressing a gap in post-disaster housing research that rarely extends beyond the emergency phase.